PENGARUH TEAM WORK, KOMITMEN ORGANISASI DAN PENGEMBANGAN TERHADAP KINERJA PEGAWAI DINAS PARIWISATA PEMUDA DAN OLAHRAGA KOTA SIBOLGA - Ade Irma Suryani; Riwayani Riwayani; Tengku Aziddin; Bayu Safri Ananda; Ratna Dewi (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
This formula research internal issue is how influence team work on employeesperformance. Howinfluence oforganization coomitment xx on employeesperformance.Howinfluence ofdevelopmenton employeesperformance. How influenceofteam work,organizationcoomitment,and developmenton employees performance. This research target is to for know influence and analyze of team work on employees performance. For know influence and analyzeof organization coomitmenton employees performance. For knowinfluenceand analyzedevelopment on employeesperformance. For know influence andanalyzeteam work,organization coomitment and development on employees performanceSample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of team work effect positive and significant on employees performance. Organization coomitment effect positive and significant on employees performance. Development effect positive and do not significant on employees performance. Team work, organization coomitment, and development effect and positive and significant on employees performanceThis formula research internal issue is how influence team work on employeesperformance. Howinfluence oforganization coomitment xx on employeesperformance.Howinfluence ofdevelopmenton employeesperformance. How influenceofteam work,organizationcoomitment,and developmenton employees performance. This research target is to for know influence and analyze of team work on employees performance. For know influence and analyzeof organization coomitmenton employees performance. For knowinfluenceand analyzedevelopment on employeesperformance. For know influence andanalyzeteam work,organization coomitment and development on employees performanceSample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of team work effect positive and significant on employees performance. Organization coomitment effect positive and significant on employees performance. Development effect positive and do not significant on employees performance. Team work, organization coomitment, and development effect and positive and significant on employees performance